UJI EFEKTIVITAS MADU KONSENTRASI 50% DAN 100% DIBANDINGKAN DENGAN POVIDONE IODINE TERHADAP PENYEMBUHAN LUKA SAYAT PADA MENCIT (MUS MUSCULUS) - M. Fahriza Winaldha Nasution; Yenita Muslimdjas (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Background: Injury is the severity of tissue continuity due to injury or surgery. To accelerate wound healing medically, an antibiotic preparation or wound covering gel can be applied, one of this is povidone iodine 10%. However, these materials have side effects and are less economical. So we need a cheaper and easier alternative to obtain, honey is one kind of option. Honey effects such as acidity, osmotic effects, chemical effects, and antimicrobial activity are the main sources in wound healing. Objective: To prove the effectiveness of wound treatment using 50% honey and 100% on wound healing compared to povidone iodine 10%. Methods: Pure laboratory experimental research. Three groups were treated for a maximum of 14 days and one group was not treated. Results: There was a significant difference between 100% Honey group with the povidone iodine 10% group while the 50% honey group had no significant difference to the povidone iodine 10% group. Conclusion: 100% Honey is more effective in healing wound cuts than 50% honey and povidone iodine 10%.